INTERNATIONAL JURISDICTION – DILEMMAS OF A SPECIFIC PROCEDURAL ISSUE - Jelena Stojsic Dabetic (Pravo)
International jurisdiction, as a special type of jurisdiction exercised by national courts or other bodies to resolve private law disputes with a foreign element, is activated whenever a relevant foreign element exists in the dispute. This foreign element may either define the civil or commercial law relationship or link the dispute to a state, or several states, other than the state of the court. Issues related to international jurisdiction fall under the domain of international civil procedural law, and the applicable procedural rules are outlined in the Law on the Resolution of Conflicts of Laws with the Regulations of Other Countries, the Law on Civil Procedure, and relevant international agreements, depending on the nature of the disputed legal issue. The legal provisions in these two laws, functioning as general (lex generalis) and special (lex specialis) laws, differ primarily in how the principle of perpetuation of jurisdiction is applied. This situation leaves practice and doctrine to provide applicable solutions. This paper will present and analyze doctrinal viewpoints and judicial practice concerning the establishment of international jurisdiction, with the aim of evaluating the proposed solution in the draft of the new Law on Private International Law. The objective of the paper is to further clarify the specific procedural situation in which courts, having established their international jurisdiction, may encounter facts that have changed during the course of the proceedings.